Prevalence and determinants of frailty in the absence of disability among older population: a cross sectional study from rural communities in Nepal - Yadav, Uday Narayan (BMC Geriatr, 2019)
BACKGROUND: Longevity and frailty have significant implications for healthcare delivery. They increase demands for healthcare service and surge risk of hospitalization. Despite gaining global attention, determinants of frailty have remained unmeasured in the rural community settings in Nepal. This study aimed to address this gap by accessing the prevalence and determinants of frailty in the absence of disability among older population living in rural communities in eastern Nepal. METHODS: We conducted a cross-sectional analytical study of 794 older adults aged ≥60 living in the rural part of Sunsari and Morang district of eastern Nepal between January and April in 2018. Multi-stage cluster sampling was applied to recruit the study participants. Study measures included socio-demographics; Frail Non-disabled scale (FiND) measuring frailty, Barthel’s Index measuring basic activities of daily living and Geriatric depression scale. Determinants of frailty in the absence of disability were identified using generalized estimating equation (GEE). RESULTS: About 65% of the participants self-reported the presence of frailty in the absence of disability. In the adjusted models, those from underprivileged ethnic groups, lack of daily physical exercise, presence of depressive symptoms and those not getting enough social support from family were found to be significantly associated with frailty among older participants. CONCLUSIONS: The prevalence of frailty in the absence of disability was high among rural community old population living in eastern Nepal. Our findings suggest that need of frailty awareness (both for clinicians and general public), so as to avoid negative consequences. To reduce the healthcare burden early screening frailty in primary care has potentials to prevent implications of frailty in Nepal.